2015
DOI: 10.3109/09638288.2015.1061607
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of Finnish children with cerebral palsy

Abstract: The used questionnaire provides an effective tool to identify areas for targeting support actions and to set goals for rehabilitation plans. The study brings forward the voices of children. It was found that pain has a great role in QOL, which should be taken into account when making rehabilitation plans. The participation of children with CP should be strengthened in every possible ways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 19 publications
5
25
0
2
Order By: Relevance
“…QOL reported by child was better than QOL reported by caregiver which was consistent with the study conducted in Finland 19 . Perhaps caregivers perceive more problems in QOL than that reported by children alone since they might perceive the child's QOL magnifi ed in view of their own diffi culties increased by the burden of a disabled family member.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…QOL reported by child was better than QOL reported by caregiver which was consistent with the study conducted in Finland 19 . Perhaps caregivers perceive more problems in QOL than that reported by children alone since they might perceive the child's QOL magnifi ed in view of their own diffi culties increased by the burden of a disabled family member.…”
Section: Discussionsupporting
confidence: 90%
“…This may be due to the poor economic condition, poor access to Health Care and lack of specialized experts to handle these problems in Nepal. Similar fi nding was seen in a study in Finland where Social wellbeing and Acceptance, emotional well-being and self-esteem were given highest point in both questionnaire versions while Pain and Impact of disability (75±17) was rated lowest in child version and Participation and Physical health (65.2±15.6) was rated lowest in Parent-proxy report 19 . Study conducted in USA also reveals that Psychosocial QOL is better in CP children 27 compared to other aspects of QOL.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, whereas in the children's questionnaires, pain was associated with age but not with the severity of the pathology, the parents associated greater frequency and intensity of pain with the severity of the pathology and the presence of epileptic crises. However, more recent studies comparing pain ratings of children with CP with those of their parents have found both overrating and underrating of pain by parents (Boling et al 2013;Ramstad et al 2011). …”
Section: Pain In Individuals With Cerebral Palsymentioning
confidence: 99%
“…The QoL of children who live with a neurological condition can be affected at different levels, including physical, psychological and psychosocial . In our previous study from 2013, the overall QoL was reported to be satisfactory in Finnish children with CP, but CP was perceived to limit participation and the pain and impact of their disability also impaired QoL in childhood . Several studies have shown that adolescence is an important time of transition, especially for individuals with a disability like CP, as many are thought to experience a decline in physical function during adolescence and early adulthood .…”
Section: Introductionmentioning
confidence: 97%